Everyone agrees - Reid, Chloë (My University, 2022)
Everyone Agrees is a collection of sixty very short stories that observe relationships between people, and between people and objects. Accompanying the stories is an essay that reflects on my personal development as a writer within the context of the contemporary art space, how this shaped my writing style, the genesis of various stories and the work of several writers and artists who draw directly from found material and their own experiences in order to explore the intricacies of human interaction.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Creative Writing to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2022